Psychological well-being of adolescents living with albinism. A case of one school in Bizana, Eastern Cape, South Africa - Azame Mqokweni; Mvuyisi Notole; Jabulani Gilford Kheswa (Interdisciplinary Journal of Education Research)
In many parts of Sub-Saharan countries such as Mozambique, Tanzania, and Malawi, research indicates that people with albinism face discrimination, violence, and death due to a deficit of melanin (pigmentation), which causes visual impairment, skin damage, and health problems. To investigate how South African adolescents living with albinism (ALWA) enhance their psychological well-being, a qualitative study was conducted utilising semi-structured interviews with twelve purposively sampled participants aged 14 to 18 years from one special school in Bizana, Eastern Cape. Inclusive Education (IE) policies and Carol Ryff’s six-dimensional theory of psychological well-being guided this study. The school principal and the participants’ legal guardians granted consent to the researchers to interview the participants. Before data collection, the researchers obtained informed consent from the participants to be audio-taped during the interviews and ensured their confidentiality and privacy. Transcribed data were coded for the identification of themes, relying on Tesch’s six steps of thematic data analysis. Participants attributed their psychological well-being to the positive school environment, parental support, and the implementation of IE policies, which contributed to their self-esteem, sense of purpose, and academic performance. Furthermore, counselling, empowerment support groups, church involvement, and emotional support from their partners indicated resilience and positive coping strategies against bullying, depression, and rejection among ALWA. These findings inform educational officials about the need to devote more resources to special schools to align with the Sustainable Development Goals of 2030, ensuring the representation of people living with albinism in tertiary institutions and beyond.